KONSEP LAYANAN PEMINATAN PADA KURIKULUM MERDEKA - Tri Cahyono; Ni Made Diah Padmi (Universitas Borneo Tarakan, 2023)
AbstractDetermining the choice of cross-subject specialization, and the choice of subject depth is a process that will involve a series of choices and decisions made by students based on an understanding of their own potential and opportunities that exist in their environment. Problems will occur if students are unable to determine the choice of specialization across subjects, and specialization deepens subject matter, so that it will hinder the learning process.The merdeka curriculum provides opportunities for students to develop their abilities, talents and interests more broadly and openly in accordance with the principle of individual differences. This allows students to develop over achievement, namely students who have a level of mastery above predetermined standards both in knowledge, attitudes, and skills. For this reason, the merdeka curriculum structure provides (1) compulsory subjects to be followed by all students in one educational unit at each educational unit and level, and (2) elective subjects which are followed by students according to their choice. Compulsory subject groups are basic subject groups that must be followed by all students contained in the merdeka curriculum structure. Keywords: Merdeka curriculum, specialization services AbstrakPenetapan pilihan peminatan lintas mata pelajaran, dan pilihan pendalaman mata pelajaran adalah sebuah proses yang akan melibatkan serangkaian pengambilan pilihan dan keputusan oleh peserta didik yang didasarkan atas pemahaman potensi diri dan peluang yang ada di lingkungannya. Permasalahan akan terjadi jika peserta didik tidak mampu untuk menetukan pilihan peminatan lintas mata pelajaran, dan peminatan pendalaman materi mata pelajaran, sehingga akan menghambat proses pembelajaran. Kurikulum merdeka memberikan kesempatan kepada peserta didik untuk mengembangkan kemampuan, bakat dan minat secara lebih luas dan terbuka sesuai dengan prinsip perbedaan individu. Ini memungkinkan peserta didik berkembang over achievement, yakni peserta didik yang memiliki tingkat penguasaan di atas standar yang telah ditentukan baik dalam pengetahuan, sikap, maupun keterampilan. Untuk itu struktur Kurikulum merdeka menyediakan (1) mata pelajaran wajib diikuti oleh seluruh peserta didik di satu satuan pendidikan pada setiap satuan dan jenjang pendidikan, dan (2) mata pelajaran pilihan yang diikuti oleh peserta didik sesuai dengan pilihan mereka. Kelompok mata pelajaran wajib merupakan kelompok mata pelajaran dasar yang harus diikuti seluruh peserta didik yang termuat dalam struktur kurikulum merdeka. Kata Kunci : Kurikulum merdeka, layanan peminatan